Ammonia-free precoated sand
By adjusting the formula of resin-coated sand, using refractory aggregates, phenolic resins, non-amine curing agents and film function improvement agents, ammonia-free coated sand was developed, which solved the ammonia emissions during the curing process of traditional resin-coated sand. and the problem of insufficient performance has achieved improvements in environmental protection, health, safety and production efficiency.
Patent Information
- Application Number
- CN202411342828.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-08
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-07
AI Technical Summary
Traditional resin-coated sand releases ammonia and other foul-odor gases during the curing process, resulting in environmental pollution and health threats. Its performance is not ideal in high-temperature environments, affecting the quality and production efficiency of castings.
An ammonia-free coated sand was developed. By adjusting the formulation of resin-coated sand, using refractory aggregates, phenolic resins, non-amine curing agents, curing accelerators and membrane function improvement agents, eliminating ammonia emissions and improving curing. Speed and durability. Specific formulas include refractory aggregates accounting for 94.5%-97.5%, phenolic resins accounting for 1%-5%, non-amine curing agents accounting for 0.15%-1.65%, curing accelerators accounting for 0.015%-0.45%, and membrane function improvement agents accounting for 0.1 %-0.35%.
It realizes the application of ammonia-free odor during the casting process, reduces the impact on workers' health, improves the casting environment, improves the quality and production efficiency of castings, reduces the scrap rate, and meets the requirements of green and environmental protection.
Smart Images

Figure CN119259909A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of casting technology, and in particular to ammonia-free coated sand. Background Art
[0002] The foundry industry is a basic industry in mechanical equipment manufacturing technology. It uses casting technology to shape metal and prepare various complex metal castings. In the casting process, sand casting is one of the main casting molding processes, which uses a large amount of resin-coated sand. Engineers feed the resin-coated sand material into a closed mold cavity, heat the resin-coated sand in the mold for a certain period of time, and then open the mold to take out the coated sand aggregate that has been solidified into the shape of the mold cavity (called sand (mold) core). This sand (mold) core with a complex structure has a certain bending resistance (called bending strength), and then different sand cores are combined into various complex sand mold structures for the manufacture of castings.
[0003] In the process of preparing sand cores with resin-coated sand, the selection of curing agent is crucial, which directly affects the performance indicators of the sand core, such as strength, hardness, heat resistance and durability. The organic amine curing agents widely used in traditional processes have fast curing and good mechanical properties, which enable the resin-coated sand to maintain sufficient strength and durability in high temperature environments. However, ammonia and other volatile gases produced by organic amine curing agents during the curing reaction not only cause serious pollution to the environment, but also pose a threat to the health of workers. Therefore, the development of ammonia-free curing agents has become a research hotspot. Although ammonia-free curing agents can effectively reduce or even eliminate the emission of ammonia in the organic amine curing reaction, their performance in practical applications (such as curing speed and slagging rate, etc.) is still far behind that of traditional organic amine curing agents. Summary of the invention
[0004] In response to the technical problems existing in the prior art, the present application proposes an ammonia-free coated sand, comprising the following raw materials in weight percentage: refractory aggregate, accounting for 94.5%-97.5%; phenolic resin, accounting for 1%-5%; non-amine curing agent, accounting for 0.15%-1.65%; curing accelerator, accounting for 0.015%-0.45%; and membrane function improver, accounting for 0.1%-0.35%.
[0005] In the ammonia-free coated sand as described above, the curing accelerator comprises the following raw materials in weight percentage: metal salts, which account for 40%-80%; and oxides, which account for 20%-60%.
[0006] The ammonia-free coated sand as described above, wherein the metal salts include: one or more of zinc salts, copper salts, calcium salts, iron salts and barium salts.
[0007] In the ammonia-free coated sand as described above, the metal salts include: one or more of calcium stearate, zinc stearate, ferric citrate, zinc chloride, zinc acetate, copper sulfate and barium carbonate.
[0008] In the ammonia-free coated sand as described above, the oxide comprises one or more of iron oxide, magnesium oxide, copper oxide, calcium oxide, zinc oxide and zirconium oxide.
[0009] In the ammonia-free coated sand as described above, the curing accelerator includes calcium stearate, zinc chloride and iron oxide; or, the curing accelerator includes zinc acetate, copper sulfate and magnesium oxide; or, the curing accelerator includes iron citrate, zinc stearate and copper oxide; or, the curing accelerator includes barium carbonate, zinc chloride and calcium oxide.
[0010] The ammonia-free coated sand as described above, wherein the curing accelerator comprises: calcium stearate: 20-50%; zinc chloride: 15-45%; iron oxide: 15-35%.
[0011] The ammonia-free coated sand as described above, wherein the film function improver is calcium stearate.
[0012] As described above, the ammonia-free coated sand, the ammonia-free resin coated sand, compared with the coated sand made of urotropine, has a nitrogen content reduced by 60%-120% under the condition of the same loss on ignition.
[0013] The ammonia-free coated sand as described above, wherein the non-amine curing agent includes: phenols, alcohols, aldehyde compounds and alkaline compounds, wherein the amount ratio of aldehydes to phenols is 1.15-1.45:1; alcohols account for 30%-70% of phenols, and alkaline compounds account for 0.5%-5% of phenols.
[0014] The ammonia-free coated sand as described above, the preparation method of the non-amine curing agent includes: weighing phenolic substances, alcohol substances, aldehyde substances and alkaline compounds and transferring them into a reactor; heating to 80-120°C to initiate the reaction, and maintaining the temperature range for continuous reaction for 1-2 hours; when the viscosity of the reactants in the reactor reaches the viscosity threshold, cooling to 50-80°C and keeping warm for 1-3 hours; vacuum dehydration, when the solid content corresponding to the reactants in the reactor reaches the solid threshold, packaging the finished product.
[0015] In the ammonia-free coated sand as described above, the phenols include: at least one of phenol, resorcinol, o-cresol, tetrabromobisphenol A, and cashew nut oil; the alcohols include: at least one of methanol, ethanol, and isopropanol; the aldehydes include: at least one of formaldehyde, acetaldehyde, benzaldehyde, and paraformaldehyde.
[0016] This application develops a new technology and product that does not release malodorous ammonia by changing the preparation formula of resin coated sand, achieving the application effect of no ammonia odor in the sand casting process. It reduces the impact on workers' health, is conducive to improving the sand casting environment, and also provides a new technological innovation for the green development of the foundry industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The preferred embodiments of the present invention will be further described in detail below with reference to the accompanying drawings, wherein:
[0018] Figure 1 is a flow chart of a method for manufacturing ammonia-free coated sand according to an embodiment of the present application;
[0019] Figure 2 yes Figure 1 Step S140 is a flow chart of the manufacturing method;
[0020] Figure 3 is a line graph of the amount of curing accelerator added and the flexural strength according to one embodiment of the present application;
[0021] Figure 4 is a line graph of the amount of membrane function improving agent added and the bending strength according to one embodiment of the present application; and
[0022] Figure 5 It is a line graph of the bending strength of coated sand manufactured by different process methods according to an embodiment of the present application. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0024] In the following detailed description, reference may be made to the various specification drawings that are part of the present application and are used to illustrate specific embodiments of the present application. In the accompanying drawings, similar reference numerals describe substantially similar components in different figures. The various specific embodiments of the present application are described below in sufficient detail so that a person of ordinary skill in the art with relevant knowledge and skills in the art can implement the technical solutions of the present application. It should be understood that other embodiments may also be used or structural, logical or electrical changes may be made to the embodiments of the present application.
[0025] In order to solve the above problems, the present application optimizes and adjusts the components and contents in the resin coated sand, and invents an ammonia-free coated sand. The ammonia-free coated sand of the present application includes the following raw materials in weight percentage: refractory aggregate, which accounts for 94.5%-97.5%; phenolic resin, which accounts for 1%-5%; non-amine curing agent, which accounts for 0.15%-1.65%; curing accelerator, which accounts for 0.015%-0.45%; and membrane function improver, which accounts for 0.1%-0.35%.
[0026] This application eliminates ammonia and other malodorous gases released during the curing reaction by readjusting the formula of ammonia-free coated sand, thereby effectively reducing air pollution and environmental burden. This not only helps to improve the working environment, but also meets the requirements of green environmental protection in my country and reduces the emission of harmful substances. In addition, ammonia-free coated sand will not release ammonia that is harmful to the human body during use, avoiding threats to the health of workers. Compared with the traditional coated sand formula, the new formula no longer emits odorous toxic and harmful substances, ensuring the health and safety of production operators. Furthermore, the curing accelerator and membrane function improver in the new formula further optimize the performance of the coated sand, giving it better strength and durability in practical applications. This improvement not only improves the quality of castings, but also reduces the comprehensive production cost of the casting process.
[0027] According to one embodiment of the present application, the curing accelerator includes the following raw materials in weight percentage: metal salts, which account for 40%-80%; and oxides, which account for 20%-60%. In other embodiments, the curing accelerator accounts for 0.018%-0.38%.
[0028] The curing accelerator comprises a solid powder mixture of metal salts and organic metal salts of various transition periods, the valence of the curing accelerator is a salt with positive valence of 2-4, and the ignition loss at 1000°C is 30-70%. Preferably, the ignition loss is 35-55%. The metal salts include one or more of zinc salts, copper salts, calcium salts, iron salts and barium salts.
[0029] In some embodiments, the nitrogen content of the ammonia-free resin coated sand is reduced by 60%-120% compared with the coated sand made of hexamethylenetetramine under the condition of the same loss on ignition.
[0030] In some embodiments, the metal salts include one or more of calcium stearate, zinc stearate, ferric citrate, zinc chloride, zinc acetate, copper sulfate and barium carbonate; the oxides include one or more of iron oxide, magnesium oxide, copper oxide and calcium oxide.
[0031] In some embodiments, the curing accelerator includes calcium stearate, zinc chloride and iron oxide; or, the curing accelerator includes zinc acetate, copper sulfate and magnesium oxide; or the curing accelerator includes iron citrate, zinc stearate and copper oxide; or the curing accelerator includes barium carbonate, zinc chloride and calcium oxide.
[0032] Furthermore, the curing accelerator includes: calcium stearate: 20-50%; zinc chloride: 15-45%; iron oxide: 15-35%.
[0033] The curing accelerator can promote the chemical reaction between phenolic resin and non-amine curing agent, accelerate the curing speed of coated sand, ensure that the coated sand forms a uniform and solid structure during the curing process, thereby improving the physical properties and high-temperature durability of the coated sand. The combination of metal salts and oxides in the curing accelerator has stable chemical properties at high temperatures, which can maintain the stability of the curing reaction and reduce possible adverse reactions during the reaction process, so that the strength and high-temperature durability of the coated sand are significantly improved, and the quality of the casting is enhanced. This not only helps to produce high-quality castings, but also reduces the scrap rate caused by insufficient material performance. Since the curing accelerator can significantly accelerate the curing reaction, production efficiency is improved and production costs are reduced accordingly.
[0034] According to one embodiment of the present application, the membrane function improver is an organic calcium salt. Further, the membrane function improver is calcium stearate.
[0035] The membrane function improver is an organic compound that can reduce the adhesion or consolidation between the resin surfaces on the resin surface, and has a molecular weight of 300-650, preferably 450-580. Its melting point is 130-200° C., preferably 140-180° C. In other embodiments, the proportion of the membrane function improver is 0.015%-0.30%.
[0036] The membrane function improver is a class of organic compounds that can form a protective film on the resin surface interface to reduce the adhesion or consolidation between resin molecules. This helps to improve the fluidity and uniformity of the coated sand during storage and use. By adjusting the physical and chemical properties of the resin surface interface, the membrane function improver can effectively improve the surface properties of the coated sand, making it show better stability and durability under high temperature conditions. The molecular weight of the membrane function improver is 300-650, preferably 450-580, so that it can form a stable and effective protective layer on the resin surface. The selection of this molecular weight range ensures its dispersibility and functionality in the coated sand. The melting point of the membrane function improver is 130-200°C, preferably 140-180°C, which enables it to effectively melt and play a role in the curing process of the coated sand, while remaining stable at room temperature. This melting point range ensures the stability and effectiveness of the membrane function improver under different temperature conditions.
[0037] According to one embodiment of the present application, the refractory aggregate includes: one or more of natural silica sand, artificial silica sand, chromite sand, zircon sand, olivine sand, and ceramic sand. The refractory aggregate is an inorganic particulate matter with a refractoriness greater than 700°C, which includes one or more selected from the following groups: metal oxides such as silicon dioxide, aluminum oxide, calcium oxide, magnesium oxide, iron oxide, titanium oxide, manganese oxide, potassium oxide, sodium oxide, zirconium oxide, nickel oxide, and chromium oxide.
[0038] The refractory aggregate particles have certain particle size groups and particle size distribution, within the particle size group range of 30 / 50, 40 / 70, 50 / 100, 70 / 140, 100 / 200, or in the form of a single group of these particle size groups or any group of groups in any proportion. Its particle size distribution satisfies the three-screen concentration rate of more than 75% and the four-screen concentration rate of 90%.
[0039] Refractory aggregates, as the main component of ammonia-free coated sand, provide the basic physical structure and mechanical strength. These aggregates can withstand high temperatures and remain stable in high temperature environments, thereby ensuring the performance of coated sand during the casting process. Refractory aggregates have high refractoriness (about 700°C and above) and can maintain their physical and chemical stability in high temperature casting environments. This ensures the heat resistance of coated sand during the casting process and prevents the aggregates from deforming or decomposing at high temperatures.
[0040] Refractory aggregates include a variety of materials, such as natural silica sand, artificial silica sand, chromite sand, zircon sand, olivine sand and ceramic sand. Each of these materials has different physical and chemical properties, and can be selected or combined according to specific casting needs to achieve the best results. Refractory aggregates are composed of various metal oxides such as silica, alumina, and calcium oxide. These components have high refractoriness and good chemical stability, and can maintain their performance in high-temperature casting environments to ensure the quality of castings. The particle size grouping and particle size distribution of refractory aggregates are carefully designed to meet the requirements of a three-screen concentration rate of more than 75% and a four-screen concentration rate of 90%. This optimized particle size distribution improves the fluidity and filling properties of the coated sand as well as the air permeability, which helps to produce castings with smooth surfaces and clear details.
[0041] According to one embodiment of the present application, the non-amine curing agent includes a phenolic polymer containing one or more of a hydroxymethyl group, a carbonyl group and an ether group, and the solid content of the phenolic polymer is 45%-70%. Further, the non-amine curing agent includes: phenols, alcohols, aldehyde compounds and alkaline compounds. Among them, the amount ratio of aldehydes to phenolic substances is (1.15-1.45): 1; alcohols account for 30%-70% of phenols; alkaline compounds account for 0.5%-5% of phenols. The alkaline compound can be an alkaline compound that reacts phenol with formaldehyde to generate a thermosetting phenolic resin, and the alkaline compound includes: one or more of sodium hydroxide, ammonia water, potassium hydroxide, and barium hydroxide.
[0042] Furthermore, the preparation method of the non-amine curing agent includes: weighing phenolic substances, alcohol substances, aldehyde substances (such as formaldehyde) and alkaline compounds and transferring them into a reactor, then heating to 80-120°C to initiate the reaction, maintaining the temperature range for continuous reaction for 1-2 hours, extracting the reactants in the reactor to test the corresponding viscosity, and when the viscosity reaches the viscosity threshold, cooling to 50-80°C, keeping warm for 1-3 hours, and then vacuum dehydrating, extracting the reactants in the reactor to test the corresponding solid content, and after reaching the solid threshold, the finished product can be discharged and packaged.
[0043] The non-amine curing agent is an organic polymer compound that does not contain amine and can undergo a curing reaction with the phenolic resin. Its molecular weight is 200-1000, preferably 300-800, and it is a viscous liquid at 25°C. The viscosity at this temperature is 150-1000 centipoise, preferably 200-500 centipoise.
[0044] According to one embodiment of the present application, the free phenol content in the phenolic resin is 0.5-5%, preferably, the free phenol content is less than 1-2.5%. The phenolic resin is a thermoplastic novolac resin prepared by the addition reaction of phenol and formaldehyde or paraformaldehyde, and its number average molecular weight is 700-2000, preferably, the molecular weight is 750-1800; the melting point of the phenolic resin is 85-105°C, preferably, the melting point is 90-100°C.
[0045] According to one embodiment of the present application, the phenols include: one or more of phenol, resorcinol, o-cresol, tetrabromobisphenol A, and cashew nut oil; the alcohols include: one or more of methanol, ethanol, and isopropanol; the aldehydes include: one or more of formaldehyde, acetaldehyde, benzaldehyde, and paraformaldehyde.
[0046] Non-amine curing agents can undergo curing reactions with phenolic resins. The active functional groups such as hydroxymethyl, carbonyl and ether groups contained in them can undergo cross-linking reactions with the functional groups in phenolic resins, thereby accelerating the curing process and improving the curing speed and efficiency of coated sand. Non-amine curing agents are viscous liquids at 25°C, with a viscosity between 150-1000 centipoise (preferably 200-500 centipoise), which ensures their stability and ease of operation at room temperature. This helps to achieve uniform mixing during the production process of coated sand and ensure the consistency of the curing effect.
[0047] The non-amine curing agent does not contain amine compounds, avoiding the harmful gases that may be released by traditional amine curing agents during use, meeting the requirements of environmental protection and health safety, and reducing the harm to operators and the environment. The solid content of phenolic polymer in the non-amine curing agent is 45%-70%, which provides sufficient reactants in the curing reaction to ensure the completeness of the reaction and the excellence of the curing effect. Its molecular weight is 200-1000 (preferably 300-800), which ensures the activity and stability of the non-amine curing agent in the reaction. The selection of this molecular weight range allows it to effectively participate in the curing reaction while maintaining appropriate fluidity and operability.
[0048] From the above, it can be seen that the ammonia-free coated sand of this application has outstanding performance in environmental protection performance, health and safety, production efficiency and product quality. In order to give full play to the advantages of ammonia-free coated sand and ensure its best effect in practical applications, a scientific and reasonable production process is crucial. Next, this application will introduce the process flow of ammonia-free coated sand to help better understand its production process and operating points. The following is the specific process flow of ammonia-free coated sand:
[0049] Figure 1 is a flow chart of a method for manufacturing ammonia-free coated sand according to an embodiment of the present application. Figure 1 As shown, the method includes:
[0050] S110, heating the refractory aggregate to 130-150°C;
[0051] S120, adding phenolic resin and stirring for a first time threshold to obtain an aggregate mixture;
[0052] S130, adding a non-amine curing agent to the aggregate mixture, and stirring for a second time threshold to obtain a curing agent mixture;
[0053] S140, adding a curing accelerator and a membrane function improver to the curing agent mixture in sequence to obtain ammonia-free coated sand;
[0054] The sum of the first time threshold and the second time threshold is between 60s and 80s.
[0055] In the method for manufacturing ammonia-free coated sand, the viscosity of the solid phenolic resin and the liquid non-amine curing agent is inconsistent when mixed, and the temperature during mixing will affect the coating effect of the product. Therefore, controlling the heating temperature of the refractory aggregate is helpful to improve the coating effect. In addition, in order to make the powdered curing accelerator evenly distributed between the refractory aggregate and the resin film, it is necessary to control the stirring time when adding the phenolic resin and the non-amine curing agent to improve the application performance of the product. Among them, the first time threshold is 10s-60s, and the second time threshold is 20s-50s.
[0056] The present application can more accurately control the reaction process and final performance of coated sand by adding non-amine curing agent, curing accelerator and membrane function improver in succession and stirring for a set time after each addition. This phased addition method helps to optimize material properties, such as improving bonding strength, reducing shrinkage, improving thermal stability or enhancing fire resistance. By accurately controlling the reaction process, the qualified rate of products can also be improved, the scrap rate can be reduced, and thus the economic benefits can be improved.
[0057] Figure 2 yes Figure 1 Step S140 of the manufacturing method flow chart is as follows: Figure 2 As shown, the method includes:
[0058] S141, adding a curing accelerator to the curing agent mixture, and stirring for a third time threshold to obtain an accelerator mixture;
[0059] S142, adding a membrane function improver to the promoter mixture, and stirring for a fourth time threshold to obtain an improver mixture;
[0060] S143, cooling and sieving the improver mixture to obtain ammonia-free coated sand.
[0061] Among them, the third time threshold is 20-40s, and the fourth time threshold is 10-20s.
[0062] This application ensures that each additive is fully mixed and evenly distributed by setting a threshold for the stirring time at each stage, thereby accurately controlling the entire reaction process and improving the performance and quality of the coated sand. The non-amine curing agent, curing accelerator and membrane function improver are added successively, and stirred for a set time after each addition to optimize the bonding strength, thermal stability and fire resistance of the ammonia-free coated sand and ensure the excellent performance of the product. By strictly controlling the time and temperature of each step, the variation in the production process is reduced, the product qualification rate is improved, the scrap rate is reduced, and the economic benefits are improved.
[0063] According to one embodiment of the present application, the accelerator mixture is subjected to a cooling treatment of 30s-90s by blowing air; the improver mixture is placed in a cooler and cooled to 30°C-60°C. By controlling the temperature, chemical reactions that may be caused by high temperature can be reduced, ensuring that the performance of the curing accelerator and the film function improver is not affected. The two cooling methods of cooling by blowing air and cooling in a cooler can ensure the stability and repeatability of the process.
[0064] Experiment 1: Screening of curing accelerator
[0065] The curing accelerator includes metal salts and oxides. The present application screens out metal salts and oxides with low agglomeration rate and fast curing speed through experimental screening. The specific test is shown in Table 1 below:
[0066]
[0067]
[0068]
[0069] The formula of embodiment 1-16 is as follows:
[0070] According to aggregate grading, a total of 8000g
[0071]
[0072] Among them, the non-amine curing agent has two formulas: Examples 1-4 and Examples 9-12 use formula (I), and Examples 5-8 and Examples 13-16 use formula (II).
[0073] Formula 1: synthesized from phenol, resorcinol, o-cresol, methanol, formaldehyde and sodium hydroxide; the material ratio follows the principle: 25.5g of phenol, resorcinol and o-cresol, 30.2g of formaldehyde, 11.8g of methanol and 0.5g of sodium hydroxide.
[0074] Formula 2: Synthesized from phenol, tetrabromobisphenol A, cashew nut oil, ethanol, formaldehyde and sodium hydroxide. The material ratio follows the principle of: phenol, tetrabromobisphenol A, cashew nut oil 25.5g, formaldehyde 30.2g, ethanol 11.8g, sodium hydroxide 0.5g.
[0075] use Figure 1 The manufacturing method in the invention produces ammonia-free coated sand, and its performance is verified as shown in Table 2 below:
[0076]
[0077]
[0078] It can be seen from Table 2 that, under the same curing accelerator, the curing rate of non-amine curing agent formula 2 is 32-560% slower than that of formula 1, but it is 1.9% faster than that of traditional coated sand, and the melting point is increased by 1°C.
[0079] Under the same non-amine curing agent scheme, the curing accelerator combination of zinc acetate / copper sulfate / magnesium oxide (Example 2, Example 6) is 52-420% more efficient in promoting the curing rate than the combination of ferric citrate / zinc stearate / copper oxide (Example 3, Example 7), and the degree of improvement in the melting point is also better than the combination of ferric citrate / zinc stearate / copper oxide (Example 3, Example 7). Both combinations have a positively correlated improvement in the melting point compared to traditional coated sand.
[0080] In the component ratio of the curing accelerator, when the salts are the same, when magnesium oxide is used in a ratio of zinc oxide, magnesium oxide can improve the anti-caking property of the coated sand better than zinc oxide.
[0081] Among the curing accelerators, the combination of calcium stearate / zinc chloride / ferric oxide (Example 1, Example 5) is more conducive to improving the curing rate of the non-amine curing agent of Formula 2, but the improvement on the melting point is low compared to the curing accelerator combinations of zinc acetate / copper sulfate / magnesium oxide (Example 2, Example 6) and ferric citrate / calcium stearate / copper oxide (Example 3, Example 7).
[0082] Among the curing accelerators, the combination of barium carbonate / zinc chloride / calcium oxide (Example 4, Example 8) is beneficial to significantly promote the curing rate of different non-amine curing agent schemes, but has a negative correlation effect on the melting point and anti-caking property of the coated sand.
[0083] Among the curing accelerators, the combination of calcium phosphate / zinc chloride / aluminum oxide (Example 9, Example 13) is insufficient in the curing promotion effect and melting point improvement on different non-amine curing agent schemes, which is a negative correlation effect. However, this combination is significantly better than Formula 1 in the anti-caking property of coated sand using Non-amine Curing Agent Formula 2.
[0084] In summary, the curing accelerator used in the present invention can be used in combination with the salts and metal oxides as curing accelerators to prepare ammonia-free coated sand with different characteristics to replace ordinary resin coated sand based on different non-amine curing agent synthesis formulas and characteristics. The present invention preferably uses non-amine curing agent formula 1 as the ammonia-free curing agent for ammonia-free coated sand, and also preferably uses zinc salts, copper salts, calcium salts, iron salts and barium salts. Further, zinc acetate, copper sulfate, calcium stearate, zinc chloride, ferric citrate and barium carbonate are prepared with magnesium oxide, zinc oxide, calcium oxide, iron oxide and zirconium oxide. These metal oxides are used to prepare environmentally friendly ammonia-free coated sand.
[0085] Experiment 2: Comparison of the characteristics of the coated sand in this application and ordinary coated sand
[0086] This application eliminates the traditional latent curing agent hexamethylenetetramine and prepares ammonia-free coated sand. Even without hexamethylenetetramine, the performance of the prepared ammonia-free coated sand can fully meet the use requirements. The following experimental verification of the performance of ammonia-free coated sand and ordinary resin coated sand yields a comparison table of the characteristics of ammonia-free resin coated sand and ordinary resin coated sand, as shown in Table 3 below:
[0087] Table 3
[0088]
[0089] Among them, the non-amine curing agent (NAG) is synthesized from phenol, resorcinol, o-cresol, methanol, formaldehyde and sodium hydroxide. The material ratio follows the principle of: phenol, resorcinol, o-cresol 25.5g in total, formaldehyde 30.2g, methanol 11.8g, sodium hydroxide 0.5g.
[0090] The curing accelerator is a mixture of calcium stearate, zinc chloride and iron oxide, wherein the calcium stearate and zinc chloride are 0.84 g in total and the iron oxide is 0.36 g.
[0091] The membrane function improver (MFI) is calcium stearate.
[0092] From the data in Table 3 above, it can be seen that the ammonia-free resin coated sand performs well in terms of instant flexural strength, room temperature flexural strength and ignition loss rate, indicating that it has better mechanical properties and high temperature stability. Compared with conventional products, the ammonia-free resin coated sand of the present application is equivalent to or better than conventional coated sand in various parameters, especially no ammonia emission, and the sand core collapse rate is increased by 18.17%; it means that the ammonia-free resin coated sand of the present application can replace conventional coated sand for casting, and there is no ammonia emission in the whole process of core making, which is a green, environmentally friendly and human health-friendly casting method.
[0093] Furthermore, the nitrogen content of the coated sand of the present application and the ordinary coated sand under the same burning loss conditions is compared.
[0094] Table 4
[0095]
[0096] Among them, the non-amine curing agent (NAG) is synthesized from phenol, resorcinol, o-cresol, methanol, formaldehyde and sodium hydroxide. The material ratio follows the principle of: 11.8g of phenol, resorcinol, o-cresol, 14.1g of formaldehyde, 5.9g of methanol, and 0.2g of sodium hydroxide.
[0097] The curing accelerator is a mixture of calcium stearate, zinc chloride and iron oxide, wherein the calcium stearate and zinc chloride are 1.92 g in total and the iron oxide is 1.28 g.
[0098] The membrane function improver (MFI) is calcium stearate.
[0099] Table 5
[0100]
[0101] Among them, the non-amine curing agent (NAG) is synthesized from phenol, resorcinol, o-cresol, methanol, formaldehyde and sodium hydroxide. The material ratio follows the principle of: 19.1g of phenol, resorcinol and o-cresol, 22.9g of formaldehyde, 9.6g of methanol and 0.4g of sodium hydroxide.
[0102] The curing accelerator is a mixture of calcium stearate, zinc chloride and iron oxide, wherein the calcium stearate and zinc chloride are 1.92 g in total and the iron oxide is 1.28 g.
[0103] The membrane function improver (MFI) is calcium stearate.
[0104] As shown in Table 4, the nitrogen content of the non-ammonia resin coated sand is reduced by 120% compared with the ordinary resin coated sand. As shown in Table 5, the nitrogen content of the non-ammonia resin coated sand is reduced by 62.5% compared with the ordinary resin coated sand, i.e., the hexamethylenetetramine coated sand.
[0105] Experiment 3: Gas phase test of the coated sand and ordinary coated sand
[0106] The gas chromatogram of the gas phase obtained by thermal cracking 100 grams of coated sand at 700°C is compared with the gas phase obtained by thermal cracking of conventional coated sand and the coated sand of the present application. The ratio of conventional coated sand to the ammonia-free coated sand of the present application is shown in Table 3.
[0107] The test results are shown in Table 6:
[0108]
[0109] As can be seen from Table 6, the coated sand of the present application reduces the emission of two gaseous substances such as amines. Compared with conventional coated sand, the total amount of gaseous substances generated by a unit of coated sand of the present application is reduced by about 28%. The thermal cracking gaseous species of the product of the present application measured at 700°C do not contain aniline, indicating that it has significant advantages in environmental performance. The total amount of gaseous substances generated by the coated sand of the present application under high temperature environment is small, showing better high-temperature stability. By eliminating the traditional latent curing agent urotropine, the coated sand of the present application not only meets the use requirements, but also outperforms conventional coated sand in many indicators.
[0110] Experiment 4: Screening of curing accelerator ratio
[0111] This application adjusts the proportion of different ingredients of the curing accelerator according to Figure 1 The ammonia-free coated sand prepared by the method in the embodiment of the present invention is tested for the performance indexes of the ammonia-free coated sand with different proportions to determine the optimal proportion of the curing accelerator. Among them, the specific components in the components of schemes 1 to 5 are the same as those in Table 3, and the specific weights of schemes 1 to 5 are different.
[0112] Solution 1
[0113] According to aggregate grading, a total of 8000g
[0114]
[0115] The test results are shown in Table 7:
[0116]
[0117] Solution 2
[0118] According to aggregate grading, a total of 8000g
[0119]
[0120]
[0121] The test results are shown in Table 8 below:
[0122]
[0123] Option 3: According to the aggregate grading, a total of 8000g
[0124]
[0125] The test results are shown in Table 9 below:
[0126]
[0127] Scheme 4: According to the aggregate grading, a total of 8000g
[0128]
[0129] The test results are shown in Table 10 below:
[0130]
[0131] Option 5
[0132] According to aggregate grading, a total of 8000g
[0133]
[0134] The test results are shown in Table 11 below:
[0135]
[0136] Experimental conclusion:
[0137] Comparing the test results of instant flexural strength and room temperature flexural strength in Tables 7-11, it can be concluded that Figure 3 A line chart in . Figure 3 It can be seen that when the optimal proportion of the curing accelerator is 0.03%, the instant flexural strength and room temperature flexural strength reach the maximum, while the melting point, ignition loss and gas emission do not change much. Furthermore, when the proportion of the curing accelerator is in the range of 0.015%-0.45%, the instant flexural strength and room temperature flexural strength meet the casting requirements. Comparing Tables 7-11, for Schemes 1 to 5, the ammonia gas emission is 0, while the melting point, ignition loss, gas emission and other indicators do not change significantly, all meeting the casting requirements.
[0138] Experiment 5: Screening of membrane function improver ratio
[0139] This application adjusts the proportion of different ingredients of the membrane function improver according to Figure 1 The ammonia-free coated sand was prepared by the method in the present invention, and the performance indicators of the ammonia-free coated sand with different ingredient ratios were tested to determine the optimal ingredient ratio of the membrane function improver.
[0140] Option 6
[0141] According to aggregate grading, a total of 8000g
[0142]
[0143] The test results are shown in Table 12 below:
[0144]
[0145] Option 7
[0146] According to aggregate grading, a total of 8000g
[0147]
[0148] The test results are shown in Table 13:
[0149]
[0150] Option 8
[0151] According to aggregate grading, a total of 8000g
[0152]
[0153] The test results are shown in Table 14 below:
[0154]
[0155] Scheme 9: According to the aggregate grading, a total of 8000g
[0156]
[0157] The test results are shown in Table 15 below:
[0158]
[0159] Scheme 10: According to the aggregate grading, a total of 8000g
[0160]
[0161]
[0162] The test results are shown in Table 16 below:
[0163]
[0164] Experimental conclusion:
[0165] Comparing the test results of instant flexural strength and room temperature flexural strength in Tables 12-16, it can be concluded that Figure 4 A line chart in . Figure 4 It can be seen that when the optimal proportion of the membrane function improver is 0.15%, the instant flexural strength and room temperature flexural strength reach the maximum. Furthermore, when the proportion of the membrane function improver is in the range of 0.1%-0.35%, the instant flexural strength and room temperature flexural strength indicators meet the casting requirements. Comparing Tables 12-16, the ammonia gas emission is 0, and the melting point, ignition loss, gas emission and other indicators do not change significantly, all meeting the casting requirements.
[0166] Experiment 6: Heating temperature of refractory aggregate
[0167] The ratios of Schemes 11 to 16 are as follows:
[0168] Through aggregate grading, a total of 8000g
[0169]
[0170] The non-amine curing agent is synthesized from phenol, resorcinol, o-cresol, methanol, formaldehyde and sodium hydroxide. The material ratio follows the principle of: 15.7g of phenol, resorcinol and o-cresol, 17.9g of formaldehyde, 7.8g of methanol and 0.16g of sodium hydroxide.
[0171] The curing accelerator is a mixture of calcium stearate, zinc chloride and iron oxide, wherein the calcium stearate and zinc chloride are 1.68 g in total and the iron oxide is 0.72 g.
[0172] The membrane function improver (MFI) is calcium stearate.
[0173] The formula of Scheme 17 is as follows:
[0174] Through aggregate grading, a total of 8000g
[0175]
[0176] Plan 11
[0177] The first step is to heat the sand to 125°C;
[0178] In the second step, environmentally friendly phenolic resin is added and the mixing time is 30 seconds;
[0179] The third step is to add non-amine curing agent and mix for 60 seconds;
[0180] Step 4: Add curing accelerator and mix for 20 seconds;
[0181] Step 5: adding membrane function improver, mixing time is 10s;
[0182] Step 6: sieve;
[0183] The seventh step is to put it into a woven bag containing a plastic inner bag to obtain an ammonia-free and environmentally friendly resin coating.
[0184] The test results are shown in Table 17 below:
[0185]
[0186] Plan 12
[0187] The first step is to heat the sand to 130°C;
[0188] In the second step, environmentally friendly phenolic resin is added and the mixing time is 30 seconds;
[0189] In the third step, non-amine curing agent is added and the mixing time is 60s;
[0190] Step 4: Add curing accelerator and mix for 20 seconds;
[0191] Step 5: adding membrane function improver, mixing time is 10s;
[0192] Step 6: sieve;
[0193] The seventh step is to put it into a woven bag containing a plastic inner bag to obtain an ammonia-free and environmentally friendly resin coating.
[0194] The test results are shown in Table 18 below:
[0195]
[0196] Plan 13
[0197] The first step is to heat the sand to 135°C;
[0198] In the second step, environmentally friendly phenolic resin is added and the mixing time is 30 seconds;
[0199] In the third step, non-amine curing agent is added and the mixing time is 60s;
[0200] Step 4: Add curing accelerator and mix for 20 seconds;
[0201] Step 5: adding membrane function improver, mixing time is 10s;
[0202] Step 6: sieve;
[0203] The seventh step is to put it into a woven bag containing a plastic inner bag to obtain an ammonia-free and environmentally friendly resin coating.
[0204] The test results are shown in Table 19 below:
[0205]
[0206] Scheme 14
[0207] The first step is to heat the sand to 145°C;
[0208] In the second step, environmentally friendly phenolic resin is added and the mixing time is 30 seconds;
[0209] In the third step, non-amine curing agent is added and the mixing time is 60s;
[0210] Step 4: Add curing accelerator and mix for 20 seconds;
[0211] Step 5: adding membrane function improver, mixing time is 10s;
[0212] Step 6: sieve;
[0213] The seventh step is to put it into a woven bag containing a plastic inner bag to obtain an ammonia-free and environmentally friendly resin coating.
[0214] The test results are shown in Table 20 below:
[0215]
[0216] Plan 15
[0217] The first step is to heat the sand to 150°C;
[0218] In the second step, environmentally friendly phenolic resin is added and the mixing time is 30 seconds;
[0219] In the third step, non-amine curing agent is added and the mixing time is 60s;
[0220] Step 4: Add curing accelerator and mix for 20 seconds;
[0221] Step 5: adding membrane function improver, mixing time is 10s;
[0222] Step 6: sieve;
[0223] The seventh step is to put it into a woven bag containing a plastic inner bag to obtain an ammonia-free and environmentally friendly resin coating.
[0224] The test results are shown in Table 21 below:
[0225]
[0226] Scheme 16
[0227] The first step is to heat the sand to 160°C;
[0228] In the second step, environmentally friendly phenolic resin is added and the mixing time is 30 seconds;
[0229] In the third step, non-amine curing agent is added and the mixing time is 60s;
[0230] Step 4: Add curing accelerator and mix for 20 seconds;
[0231] Step 5: adding membrane function improver, mixing time is 10s;
[0232] Step 6: sieve;
[0233] The seventh step is to put it into a woven bag containing a plastic inner bag to obtain an ammonia-free and environmentally friendly resin coating.
[0234] The test results are shown in Table 22:
[0235]
[0236] Scheme 17 (control group)
[0237] The first step is to heat the sand to 120℃;
[0238] In the second step, phenolic resin was added and the mixing time was 70s;
[0239] In the third step, an amine curing agent (urotropine) was added and the mixing time was 50 seconds;
[0240] Step 4: Add the release agent and mix for 20 seconds;
[0241] Step 5: sieve;
[0242] The sixth step is to put the sand into a woven bag containing a plastic inner bag to obtain resin coated sand.
[0243] The test results are shown in Table 23:
[0244]
[0245] Summary: Summarizing the data in Tables 17-23, we can obtain the following Table 24:
[0246]
[0247]
[0248] Combining Table 23 and Table 24, it can be seen that when the heating temperature of the sintered sand (refractory aggregate) is between 130℃ and 150℃, the instant flexural strength, room temperature flexural strength, melting point and other indicators of the coated sand can reach or even exceed the performance indicators of the traditional process (control group), which meets the production requirements of the coated sand. Furthermore, when the heating temperature of the sintered sand is around 135℃, the performance indicators of the coated sand are the best.
[0249] Experiment 7: Mixing time of adding phenolic resin and non-amine curing agent
[0250] The ratios of Schemes 18 to 22 are as follows:
[0251] Through aggregate grading, a total of 8000g
[0252]
[0253] The non-amine curing agent is synthesized from phenol, resorcinol, o-cresol, methanol, formaldehyde and sodium hydroxide. The material ratio follows the principle of: 15.7g of phenol, resorcinol and o-cresol, 17.9g of formaldehyde, 7.8g of methanol and 0.16g of sodium hydroxide.
[0254] The curing accelerator is a mixture of calcium stearate, zinc chloride and iron oxide, wherein the calcium stearate and zinc chloride are 1.68 g in total and the iron oxide is 0.72 g.
[0255] Membrane function improver (MFI) is calcium stearate
[0256] Plan 18
[0257] The first step is to heat the sand to 140°C;
[0258] In the second step, environmentally friendly phenolic resin is added and the mixing time is 10 seconds;
[0259] In the third step, non-amine curing agent is added and the mixing time is 50s;
[0260] Step 4: Add curing accelerator and mix for 20 seconds;
[0261] Step 5: adding membrane function improver, mixing time is 10s;
[0262] Step 6: sieve;
[0263] The seventh step is to put it into a woven bag containing a plastic inner bag to obtain an ammonia-free and environmentally friendly resin coating.
[0264] The test results are shown in Table 25 below:
[0265]
[0266] Plan 19
[0267] The first step is to heat the sand to 140°C;
[0268] In the second step, environmentally friendly phenolic resin is added and the mixing time is 20 seconds;
[0269] In the third step, non-amine curing agent is added and the mixing time is 40s;
[0270] Step 4: Add curing accelerator and mix for 20 seconds;
[0271] Step 5: adding membrane function improver, mixing time is 10s;
[0272] Step 6: sieve;
[0273] The seventh step is to put it into a woven bag containing a plastic inner bag to obtain an ammonia-free and environmentally friendly resin coating.
[0274] The test results are shown in Table 26:
[0275]
[0276] Plan 20
[0277] The first step is to heat the sand to 140°C;
[0278] In the second step, environmentally friendly phenolic resin is added and the mixing time is 40 seconds;
[0279] In the third step, non-amine curing agent is added and the mixing time is 20 seconds;
[0280] Step 4: Add curing accelerator and mix for 20 seconds;
[0281] Step 5: adding membrane function improver, mixing time is 10s;
[0282] Step 6: sieve;
[0283] The seventh step is to put it into a woven bag containing a plastic inner bag to obtain an ammonia-free and environmentally friendly resin coating.
[0284] The test results are shown in Table 27 below:
[0285]
[0286] Plan 21
[0287] The first step is to heat the sand to 140°C;
[0288] In the second step, environmentally friendly phenolic resin is added and the mixing time is 60 seconds;
[0289] In the third step, non-amine curing agent is added and the mixing time is 20 seconds;
[0290] Step 4: Add curing accelerator and mix for 20 seconds;
[0291] Step 5: adding membrane function improver, mixing time is 10s;
[0292] Step 6: sieve;
[0293] The seventh step is to put it into a woven bag containing a plastic inner bag to obtain an ammonia-free and environmentally friendly resin coating.
[0294] The test results are shown in Table 28:
[0295]
[0296] Plan 22
[0297] The first step is to heat the sand to 140°C;
[0298] In the second step, environmentally friendly phenolic resin is added and the mixing time is 70 seconds;
[0299] In the third step, non-amine curing agent is added and the mixing time is 20 seconds;
[0300] Step 4: Add curing accelerator and mix for 20 seconds;
[0301] Step 5: adding membrane function improver, mixing time is 10s;
[0302] Step 6: sieve;
[0303] The seventh step is to put it into a woven bag containing a plastic inner bag to obtain an ammonia-free and environmentally friendly resin coating.
[0304] The test results are shown in Table 29 below:
[0305]
[0306] Summary: Summarizing the data in Tables 25-29, we can obtain the following Table 30:
[0307]
[0308] As can be seen from the above table, when the sum of the mixing time of adding phenolic resin and non-amine curing agent is between 60s and 80s, the stirring time after adding phenolic resin is 10s-60s, and the stirring time after adding non-amine curing agent is 20s-50s, the performance indicators of the products meet the production requirements. When the mixing time of adding phenolic resin and non-amine curing agent is too long, the mixing state of phenolic resin and non-amine curing agent is not conducive to the uniform distribution of curing accelerator, thereby affecting the performance indicators of coated sand.
[0309] When phenolic resin is used with non-amine curing agent to prepare coated sand, the glassy thermoplastic phenolic resin is first heated and gradually changes from a solid glassy state to a warm viscous state. The viscosity of the warm viscous state gradually decreases with the increase of heating time. When the mixing time reaches a certain length, the rheological viscosity of the thermoplastic resin forms a homogenized rheological body. At this time, the resin rheological body has a certain stable viscosity value due to the deformation of the mechanical shear rate. When the non-amine curing agent is heated, its original low-viscosity rheological state will gradually increase with the volatile viscosity of the solvent when heated, and its viscosity will have a stable value after reaching a certain length of time.
[0310] When the thermoplastic resin and the non-amine curing agent are heated under the same temperature conditions, the rheological state formed by the thermoplastic resin and the non-amine curing agent reaches the respective stable viscosity values at a certain rate. In addition, there is a certain difference in the viscosity value when the stable viscosity state is reached. Therefore, the stirring time after adding the phenolic resin and the stirring time after adding the non-amine curing agent will determine the viscosity values of the two. The difference in the viscosity values of the two will affect the microscopic homogeneity of the phenolic resin and the non-amine curing agent of the coated sand, the thickness uniformity of the film, the film formation stability of the film, and the uniformity of the distribution of the solid micropowder curing accelerator in the film. Under certain environmental conditions such as mixing temperature and mixing mechanical action intensity, too long mixing time and too short mixing time will seriously affect the performance of the coated sand. Therefore, when the sum of the mixing time of adding phenolic resin and non-amine curing agent is between 60s-80s, the stirring time after adding the phenolic resin is 10s-60s, and the stirring time after adding the non-amine curing agent is 20s-50s, the difference in the viscosity values of the two can be reduced and the performance indicators of the coated sand can be improved.
[0311] Experiment 8: Component addition order and temperature reduction verification
[0312] The ratios of Scheme 23 to Scheme 25 are as follows:
[0313] According to the aggregate grading, a total of 8000g
[0314] Refractory aggregate: 7749.6g 96.87% (weight ratio)
[0315] Phenolic resin (PF1891): 160g 2.0% (weight ratio)
[0316] Non-amine curing agent (NAG): 68g 0.85% (weight ratio)
[0317] Curing accelerator (Z6): 2.4g 0.03% (weight ratio)
[0318] Membrane function improver (MFI): 20g 0.25% (weight ratio)
[0319] Among them, the non-amine curing agent (NAG) is synthesized from phenol, resorcinol, o-cresol, methanol, formaldehyde and sodium hydroxide. The material ratio follows the principle of: phenol, resorcinol, o-cresol 25.5g in total, formaldehyde 30.2g, methanol 11.8g, sodium hydroxide 0.5g.
[0320] The curing accelerator is a mixture of calcium stearate, zinc chloride and iron oxide, wherein the calcium stearate and zinc chloride are 1.68 g in total and the iron oxide is 0.72 g.
[0321] The membrane function improver (MFI) is calcium stearate.
[0322] Plan 23
[0323] The process methods include:
[0324] The first step is to heat the sand to 140°C;
[0325] The second step is to add environmentally friendly phenolic resin;
[0326] The third step is to add non-amine curing agent, curing accelerator and membrane function improver;
[0327] Step 4: Mixing time is 10s;
[0328] Step 5: sieve;
[0329] The sixth step is to put it into a woven bag containing a plastic inner bag to obtain ammonia-free and environmentally friendly resin coated sand.
[0330] The test results are shown in Table 31 below:
[0331]
[0332] Scheme 24
[0333] The first step is to heat the sand to 140°C;
[0334] In the second step, environmentally friendly phenolic resin is added and the mixing time is 25 seconds;
[0335] In the third step, non-amine curing agent is added and the mixing time is 75 seconds;
[0336] Step 4: Add curing accelerator and mix for 10 seconds;
[0337] Step 5: adding membrane function improver, mixing time is 10s;
[0338] Step 6: sieve;
[0339] The seventh step is to put it into a woven bag containing a plastic inner bag to obtain an ammonia-free and environmentally friendly resin coating. The test results are shown in the following table 32:
[0340]
[0341] Scheme 25
[0342] The first step is to heat the sand to 140°C;
[0343] In the second step, environmentally friendly phenolic resin is added and the mixing time is 25 seconds;
[0344] In the third step, the sand temperature is lowered to 110°C, a non-amine curing agent is added, and mixed for 25 seconds;
[0345] Step 4: Add curing accelerator and mix for 10 seconds;
[0346] Step 5: Blow cold air to cool down, and the duration of blowing cold air is 40s;
[0347] Step 6: Add membrane function improver and mix for 10 seconds;
[0348] Step 7: sieve and cool to 35°C in a cooler;
[0349] Step 8: sieve;
[0350] The ninth step is to put it into a woven bag containing a plastic inner bag to obtain ammonia-free and environmentally friendly resin coated sand.
[0351] The test results are shown in Table 33:
[0352]
[0353] Conclusion: Reference Figure 5 Compared with Scheme 23, Scheme 24 optimizes the steps of adding non-amine curing agent, curing accelerator and membrane function improver, that is, adding them together is changed to adding them in sequence, and mixing for a period of time after each addition. Compared with Scheme 23, Scheme 24 has significantly improved the instant flexural strength and room temperature flexural strength, and the ammonia gas emission of both is 0.
[0354] Compared with Scheme 24, Scheme 25 uses cold air to cool down after adding the curing agent accelerator, and enters the cooler to cool down to 35° C. Compared with Scheme 24, Scheme 25 has significantly improved instant flexural strength and room temperature flexural strength, and the ammonia gas emission of both is 0.
[0355] The above embodiments are only used to illustrate the present application, and are not intended to limit the present application. Ordinary technicians in the relevant technical field may make various changes and modifications without departing from the scope of the present application. Therefore, all equivalent technical solutions should also fall within the scope disclosed in the present application.
Claims
1. An ammonia-free coated sand comprising the following raw materials in percentage by weight: Refractory aggregate, which accounts for 94.5%-97.5%; Phenolic resin, accounting for 1%-5%; Non-amine curing agent, which accounts for 0.15%-1.65%; A curing accelerator, which accounts for 0.015% to 0.45%; and Membrane function improver, its proportion is 0.1%-0.35%.
2. The ammonia-free coated sand according to claim 1, wherein the curing accelerator comprises the following raw materials in weight percentage: Metal salts, accounting for 40%-80%; and Oxides account for 20%-60%.
3. The ammonia-free coated sand according to claim 2, wherein the metal salts include: One or more of zinc salt, copper salt, calcium salt, iron salt and barium salt.
4. The ammonia-free coated sand according to claim 2, wherein the metal salts include: One or more of calcium stearate, zinc stearate, ferric citrate, zinc chloride, zinc acetate, copper sulfate and barium carbonate.
5. The ammonia-free coated sand according to claim 2, wherein the oxide comprises: One or more of iron oxide, magnesium oxide, copper oxide, calcium oxide, zinc oxide and zirconium oxide.
6. The ammonia-free coated sand according to claim 4 or 5, wherein the curing accelerator comprises calcium stearate, zinc chloride and iron oxide; or The curing accelerator includes zinc acetate, copper sulfate and magnesium oxide; or The curing accelerator includes ferric citrate, zinc stearate and copper oxide; or The curing accelerator includes barium carbonate, zinc chloride and calcium oxide.
7. The ammonia-free coated sand according to claim 4 or 5, wherein the curing accelerator comprises: Calcium stearate: 20-50%; Zinc chloride: 15-45%; Iron oxide: 15-35%.
8. The ammonia-free coated sand according to claim 1, wherein the film function improver is calcium stearate.
9. The ammonia-free coated sand according to claim 1, wherein the nitrogen content of the ammonia-free resin coated sand is reduced by 60%-120% compared with the coated sand made of hexamethylenetetramine under the condition of the same loss on ignition.
10. The ammonia-free coated sand according to claim 1, wherein the non-amine curing agent comprises: Phenols, alcohols, aldehyde compounds and alkaline compounds, wherein the amount ratio of aldehydes to phenols is 1.15-1.45:1; alcohols account for 30%-70% of phenols, and alkaline compounds account for 0.5%-5% of phenols.
11. The ammonia-free coated sand according to claim 10, wherein the preparation method of the non-amine curing agent comprises: Weigh phenolic substances, alcoholic substances, aldehyde substances and alkaline compounds and transfer them into a reaction kettle; Raise the temperature to 80-120°C to initiate the reaction, and maintain this temperature range for 1-2 hours; When the viscosity of the reactants in the reactor reaches the viscosity threshold, cool down to 50-80°C and keep warm for 1-3 hours; Vacuum dehydration: when the solid content of the reactants in the reactor reaches the solid threshold, the finished product is packaged.
12. The ammonia-free coated sand according to claim 10, wherein the phenols include: At least one of phenol, resorcinol, o-cresol, tetrabromobisphenol A, and cashew nut oil; The alcohols include at least one of methanol, ethanol and isopropanol; the aldehydes include at least one of formaldehyde, acetaldehyde, benzaldehyde and paraformaldehyde.